Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s11325-018-1685-8
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality and influencing factors among rural adults in Deqing, China

Abstract: Sleep problems were prevalent among the rural Chinese adults aged 45+ years. People who were unmarried or had low personal income or any chronic diseases were more likely to have poor sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
6
31
1
2
Order By: Relevance
“…Among the seven PSQI domains, sleep latency was most highly prevalent (39.7%), followed by sleep duration (31.0%) and habitual sleep efficiency (28.8%). These results were slightly different from those of other rural adults or the elderly in other provinces in China [29,31]. Variations in diagnostic criteria, interview techniques, and age of the study populations may also partly contribute to the inconsistent results across studies.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Among the seven PSQI domains, sleep latency was most highly prevalent (39.7%), followed by sleep duration (31.0%) and habitual sleep efficiency (28.8%). These results were slightly different from those of other rural adults or the elderly in other provinces in China [29,31]. Variations in diagnostic criteria, interview techniques, and age of the study populations may also partly contribute to the inconsistent results across studies.…”
Section: Discussioncontrasting
confidence: 69%
“…The epidemiologic studies have indeed frequently indicated that female gender is an independent risk factor for sleep disorders [35,36]. The reason for poor sleep in women may be due to the fact that compared to men, women had higher proportions of low education, low individual income, and more chronic diseases, and were more susceptible to depression and anxiety [5,31,37].…”
Section: Discussionmentioning
confidence: 99%
“…Information about demographic characteristics, COVID-19 and lifestyle was collected by the selfstructured questionnaire. Questions on lifestyle factors, including regular alcohol drinking (> 3 times/week for ≥ 6 months) (17), regular cigarette smoking (> 3 times/week for ≥ 6 months) (18), regular tea drinking (> 3 times/week for ≥ 6 months) (19) and regular physical activity (> 10 min/day for ≥ 6 months) (20) were designed according to previous epidemiological researches. COVID-19 related information included quarantine status, awareness of COVID-19, self-protection measures and history of vaccination.…”
Section: Measures Of Quality Of Life and In Uencing Factorsmentioning
confidence: 99%
“…Another cross-sectional survey among Inner Mongolia Medical University students found that exercise less than three times a week and skipping breakfast were associated with poor sleep quality [8]. Some research investigated sleep quality and its associated factors among rural adults [9,10], low-income rural adults [11], rural elderly [12,13]. A cross-sectional survey conducted in Deqing County of China reported that rural people who were unmarried or had low personal income or any chronic diseases were more likely to have poor sleep quality [9].…”
mentioning
confidence: 99%
“…Some research investigated sleep quality and its associated factors among rural adults [9,10], low-income rural adults [11], rural elderly [12,13]. A cross-sectional survey conducted in Deqing County of China reported that rural people who were unmarried or had low personal income or any chronic diseases were more likely to have poor sleep quality [9]. Another study among rural adults in Henan province of China showed that older age, being female, unmarried/divorced/widowed, low education level, low income, drinking, depression and dyslipidemia could increase the odds of poor sleep quality [10].…”
mentioning
confidence: 99%